The Influence of Customer Experience and Trust on Repeat Purchase Interest in the Shopee Marketplace - Iqbal Muhaemin; Baghiz Abbiyu Dzaky; Lis Tatin Hernidatiatin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of customer experience and trust on repurchase interest in the Shopee marketplace. In February 2023, there was a decline, indicating that e-commerce faces challenges in maintaining customer loyalty and that consumers are starting to be more selective in choosing shopping platforms. This research is a quantitative study with a survey method. Data collection was carried out using a questionnaire instrument; the number of samples used was 404 respondents. The analysis technique used is Structural Equation Modeling - Partial Least Squares (SEM-PLS) with SmartPLS 3.0 software. The results of the study show that customer experience has a significant influence on repurchase interest with a path coefficient of 0.211. Trust also has a positive and significant effect on repurchase interest with a path coefficient of 0.447. Simultaneously with an F-count value of 83.09, which is greater than the F-table of 3.02, the customer experience and trust variables have a positive and significant effect on repurchase interest.